2016
DOI: 10.1590/1678-457x.0085
|View full text |Cite
|
Sign up to set email alerts
|

Lactose hydrolysis potential and thermal stability of commercial β-galactosidase in UHT and skimmed milk

Abstract: The commercial enzyme (E.C. = 3.2.1.23) from Kluyveromyces lactis (liquid) and Aspergillus oryzae (lyophilized) was investigated for its hydrolysis potential in lactose substrate, UHT milk, and skimmed milk at different concentrations (0.7; 1.0 and 1.5%), pH values (5.0; 6.0; 6.5 and 7.0), and temperature (30; 35; 40 and 55 ºC). High hydrolysis rates were observed for the enzyme from K. lactis at pH 7.0 and 40 ºC, and from A. oryzae at pH 5.0 and 55 ºC. The enzyme from K. lactis showed significantly higher hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 19 publications
0
16
0
3
Order By: Relevance
“…Lactose in whole and skim milk decreased (p<0.001) at the end of the fermentation process although milk is a source of lactose [17] (Table 1). Leite et al [3] also observed the same result when using whole milk and kefir.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…Lactose in whole and skim milk decreased (p<0.001) at the end of the fermentation process although milk is a source of lactose [17] (Table 1). Leite et al [3] also observed the same result when using whole milk and kefir.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…Despite the recent researches on dairy technology, science and nutrition (Akal & Yetişemiyen, 2016;Barbosa et al, 2013;Bosso et al, 2016;Hamoudi-Belarbi et al, 2016;Mostafidi et al, 2016;Rangel et al, 2016;Sales et al, 2016), there are few information's published on the sweetened condensed milk subject.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Holsinger;Kligerman (1991), os sintomas de intolerância a lactose podem ser eliminados quando no mínimo, 70% da mesma é reduzida. Neste sentido, Bosso et al (2016) No Brasil, a Instrução que regulamenta as condições de produção, identidade e os requisitos mínimos de qualidade de leite caprino, destinado ao consumo humano, estabelece como padrões mínimos: 2,8% de proteína bruta, 4,3% de lactose, 8,20% de sólidos não gordurosos e 0,7% de cinzas, acidez de 0,13% a 0,18%; densidade a 15°C de 1,028 g/mL a 1,034 g/mL; índice crioscópico (ponto de congelamento) de -0,550ºH a -0,585ºH; e pH mínimo em torno de 6,4 (BRASIL, 2000).…”
Section: Fundamentação Teóricaunclassified